Analisis Kepuasan Pengguna Mobile E-Health berdasarkan Metode End User Computing Satisfaction (Studi di 5 Puskesmas di Kota Surabaya) - Fitri Azzahrah; Yesicha Aprillia Putri Adian; Wasis Budiarto (Politeknik Kesehatan Tanjung Karang, 2020)
The internet-based technology development is beneficial for all sectors, including the health sector. For example, the Primary Healthcare Center. Primary Healthcare Center, provides health services with various health programs to fulfill the community's needs. A program in which The Primary Healthcare Center uses internet-based technology is e-health. E-health is a service designed for the public which is a combination of information and communication technology applications that are connected to all functional elements that support the health sector as their knowledge base. E-health has been enforced in 63 Primary Healthcare Centers in Surabaya. This study aims to analyze the use and satisfaction of mobile e-health in 5 Primary Healthcare Centers in Surabaya base on the End User Computing Satisfaction (EUCS) Method. EUCS consists of 5 variables, which are content, accuracy, format, ease of use, and timeliness. This study was designed as an observational study in Primary Healthcare Center patients using mobile e-health as a population. The study involved 100 patients in 5 health centers in Surabaya. The sample was selected using a random sampling method. The results of the study point out that all respondents were satisfied with the e-health mobile application, however, gaps still occur in each EUCS variable. This is due to the reality does not meet the expectations. The biggest gap is in the timeliness variable, which is 0,6. Due to the gap between reality and expectations. To increase user satisfaction, evaluation is needed to be done. Such as, strengthen the mobile application’s system, to achieve the user’s expectation and minimize the gap between expectations and reality. Simplification of usage and motivation procedures for the community should be continued so that the use of e-health mobile can cover all Surabaya citizens.